Impact of the Board on Management of Lithuanian State Owned Enterprises - Jurkonis, Liudas; Aničas, Ignas (Ekonomika, 2015)
The article concentrates on the main challenge tackled by the state-owned enterprises (SOEs) reform initiated by the 15th government of the Republic of Lithuania – an attempt to improve the corporate governance practices and management efficiency of Lithuanian SOEs. According to the insights offered by the new public management (NPM) paradigm, resource dependency theory (RDT) and principal-agent theory (PAT), the present research seeks to identify a quantifiable relationship between the composition of the board (which is one of the core aspects of the Lithuanian SOE reform) and return on equity (ROE) in Lithuanian SOEs (which is selected to be the key variable defining management efficiency). Based on key relationships among the selected parameters of the board (e.g., size, political independency, gender diversity, other) and SOE management efficiency identified, this paper offers practical public policy recommendations in the field of SOE management efficiency.